Directive Speech Acts Addressed to Bride and Groom in Sawer Panganten Lyrics: A Pragmatic Analysis - Persada Gemilang, Najwa Baruna Bunga; Djuharie, Otong Setiawan; Saehu, Andang (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study looks at directive speech acts in the lyrics of Sawer Panganten, a Sundanese wedding ritual song, using Searle's (1969, 1979) Speech Act Theory together with Leech's (1983) Politeness Principle. Dewi et al. (2024) recently classified illocutionary speech acts in a single sawér poem from Ciamis, but that study did not look at how directive force is distributed between the bride and the groom, and it did not check the written text against an actual recorded performance. This study tries to fill that gap. The main data come from the written performance text Kidung Sawer Panganten (Pa Uhi 1–4), and this is checked against a transcribed excerpt from a recorded performance by a practising sinden. After getting feedback on translation accuracy, the directive markers, especially ulah and sing, were looked at again and placed along a continuum from strong prohibition to gentle advice rather than treated as if they all carried the same prohibitive force. In total, 47 directive instances were identified and sorted into seven categories. The bride (Eulis) still receives a numerical majority of the directives (55%), but the force behind those directives turns out to be more varied than a simple word count would suggest. A number of ulah-marked lines actually function more like affectionate advice than strict prohibition. Checking the written text against the recorded performance confirms that the main directive markers show up in both sources, and it also reveals additional directive content addressed to the groom about household leadership that is not present in the written text. Overall, the findings build on existing scholarship on Sundanese sawér by showing that gendered asymmetry in this kind of ritual speech is not just a matter of how often directives appear, but also of how strong and how harsh they are.